Laser surface hardening of bearing steels - Maharjan, Niroj (2019)
Laser surface hardening has emerged as a promising technique to improve the wear resistance of machine components such as bearings, gears and camshafts. However, a lack of thorough understanding of the underlying mechanism coupled with the stringent requirements on surface properties still hinders its widespread application in industries. This thesis investigates various aspects of laser surface hardening of bearing steels (such as effect of operating parameters and laser types, microstructural changes, corrosion properties and improving effectivity) with an aim to elaborate the underlying mechanism and improve surface properties.